Thrombotic Thrombocytopenic Purpura associated with Pembrolizumab. (June 2022) - Nelson, Derrick; Kodsi, Marina; Cockrell, Dillon; Morgan, Jennifer; Key, Nigel
Introduction: Thrombotic thrombocytopenic purpura (TTP) is a life threatening type of thrombotic microangiopathy (TMA) caused by a deficiency in ADAMTS13. Here, we describe a case of TTP in association with pembrolizumab treatment for metastatic urothelial carcinoma. Case report: Our patient was a 68-year-old male who received three cycles of pembrolizumab. Shortly after he developed an acute onset of numbness of the right side of his arm and face, slurred speech, generalized weakness, loss of appetite and shortness of breath. Initial laboratory changes in emergency department revealed hyponatremia, elevation in blood urea nitrogen (BUN) and serum creatinine, decreased hemoglobin, significant thrombocytopenia and leukocytosis. His thrombocytopenia continued to worsen, reaching low levels of 19, 000 × 10 9 /L. Given the presence of schistocytes, a PLASMIC score was calculated (5). ADAMTS13 activity and inhibitor returned 8% (ref. >80%) and 3% (ref. <0.4%), respectively. The patient passed away. Management & outcome: He received two 500 mL normal saline boluses and 1 unit of packed red blood cells (pRBC) as well as an extensive imaging workup. On admission, his renal function and platelet counts continued to decline. Given multiple comorbitidies his family opted out of further treatment and the patient ultimately passed away. Discussion: Pembrolizumab could possibly induce TMA. In this case the abnormal ADAMTS13 activity level makes TTP more likely, though through an unknown mechanism. Although immunotherapies play an important role in the field of oncology, the effects are not entirely cell specific and unwarranted treatment related complications should be considered.